Treatment of Typhoid Fever in Children: Comparison of Efficacy of Ciprofloxacin with Ceftriaxone - Naveed, Amna; Ahmed, Zeeshan (European Scientific Journal, ESJ, 2016)
Objective: To compare the clinical efficacy of ciprofloxacin vs ceftriaxone in terms of the proportion of children becoming afebrile in 96 hours. Study Design: Randomized controlled design study. Place and Duration of Study: Department of Pediatrics, Holy Family Hospital, Rawalpindi from March 2010 to September 2010. Methodology: 88 children who fulfilled the clinical criteria of having typhoid fever were included in the study. They came to the indoor and outdoor of the department. 44 patients were treated with injectable ciprofloxacin, while 44 were treated with injectable ceftriaxone. Results: The study included 88 patients with febrile illness who were suspected of having typhoid fever. The mean age was 8.3±1.94 years and 41 (46.6%) were males. The mean weight was 24.7±6.3 kg. Only 15 (17%) used boiled water as a routine. 68 (77.3%) children in total became afebrile within 96 hours and 20 (22.7%) failed to become afebrile in 96 hours. In the ciprofloxacin group, 25 (56.8%) patients became afebrile in 96 hours and 19 (43.1%) failed to become afebrile in 96 hours. In the ceftriaxone group, 43 (97.7%) patients became afebrile in 96 hours and 1 (2.3%) failed to become afebrile in 96 hours. The proportion of patients becoming afebrile within 96 hours was significantly higher in the ceftriaxone group as compared to the ciprofloxacin group, p= 0.00. Conclusion: Ceftriaxone is more effective in children with typhoid fever in terms of greater proportion of children becoming afebrile in 96 hours.